Поетичний світ Бориса Грінченка - Левчик, Н.В. (Слово і Час, 2019)
У статті проаналізовано етапи творчого становлення Бориса Грінченка як поета. Образно-
тематична, стильова, жанрова характеристика його поетичної творчості розглядається впродовж
трьох вимірів: рання поезія 1880-х років, вірші 1890-х та 1900-х років. У полі зору динаміка
розвитку образу ліричного героя. Приділена увага версифікаційній будові вірша. The paper focuses on the figurative, style, and genre characteristics of B. Hrinchenko’s poetry.
Three stages have been distinguished: early poetry of the 1880s, poems of the 1890s, and those of
the1900s. The first period is marked by a thematic and formal imitation of T. Shevchenko, I. Manzhura,
V. Zabila, etc., and yet the originality of poetic talent, attested by the poems “The Tiller”, “Sad Views”,
and others, is evident. In terms of genre and style, the civic poetry prevails, in which the leading motive
is work, sometimes interpreted as commitment to the benefit of others (1880s), and sometimes as an
immanent internal need of an individual (1900s). The researcher traces the dynamics of the lyric hero,
being defined mostly by the moral imperative. In B. Hrinchenko’s poetry of the late 1890s, philosophy
and sensuality deepened, and as a consequence the lyrical hero changed; the strong-willed personality
with a neo-romantic outlook emerges. The topicality of neo-romantic ideas for the poet is indicated by
the interpretation of the motive of spiritual leadership, as a feature that characterizes someone who
is able to elevate others to his level.
The syncretism of the types of artistic understanding of reality is evident in Hrinchenko’s poems.
The poems of the 1880s and 1890s were dominated by the positivist worldview, and the poetry at the
turn of the century was rather focused on the subjective and emotional, neo-romantic perception of
the world, although not devoid of the ‘two worlds’ concept of the late romanticism.
Meditative and epical lyrics noticeably prevail in Hrinchenko’s genre system, due both to the thematic
material and the focus on the reader. The most frequent were reflection, appeal, invective, and song
genres, mainly romance, for example “The Soul is Burning, and the Heart is Singing.”
Knowledge of folklore, interest in the Cossack era and the history of the Cossack state gave
Hrinchenko material for his works; he wrote about twenty poems interpreting the history of Ukraine.